Personality Traits and Leadership Effectiveness. A Mini Review - Koutsioumpa, Eftichia (Technium Education and Humanities, 2023)
The analysis of the relationship between personality traits and leadership effectiveness has been a central area of investigation within organizational psychology for an extended period. This review aims to examine the impact of fundamental personality traits on leadership effectiveness. Based on empirical findings derived from the Five-Factor Model (FFM), it has been observed that specific personality traits, namely conscientiousness and emotional stability, exhibit consistent associations with effective leadership behaviors. Conscientious leaders exhibit traits such as organization, diligence, and responsibility, which in turn contribute to enhanced decision-making capabilities and the successful execution of projects. Emotional stability enables leaders to effectively manage and navigate the various stressors encountered in the workplace, demonstrating composure and a clear understanding of the situation. Openness to experience, a personality trait identified in the Five-Factor Model (FFM), has the potential to facilitate innovative thinking and adaptability, both of which are crucial for effectively navigating the dynamic challenges of the business environment. Nevertheless, it is widely agreed upon that these characteristics hold significant value. Nonetheless, the ideal equilibrium of these traits differs depending on the specific circumstances, sectors, and societal norms. There is also evidence from research suggesting that situational factors and individual experiences may moderate the influence of personality. In summary, personality traits are a fundamental framework for assessing leadership potential. However, it is essential to recognize that the expression and influence of these traits are complex and varied, thus necessitating a comprehensive approach to cultivating leadership skills. This systematic review aims to compile a comprehensive body of evidence spanning thirteen years, focusing on the impact of personality traits on leadership performance. The study examines various personality traits, including extroversion, approachability, receptivity to new experiences, neuroticism, conscientiousness, narcissism, honesty-humility, approach to risk, and tolerance of ambiguity. A significant positive correlation was observed between effectiveness and all traits mentioned above except neuroticism and, in certain instances, narcissism. The results of our study can serve as a basis for future investigations in this field.